2015
DOI: 10.1097/01.npr.0000460853.60234.c2
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting reversible contraceptives for teenagers

Abstract: Long-acting reversible contraceptive (LARC) methods are underutilized in the adolescent population despite their superior efficacy over non-LARC methods. The purpose of this article is to discuss the barriers that lead to underutilization of these methods and present an evidence-based approach for the use of LARC methods among adolescents in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
0
9
0
5
Order By: Relevance
“…In the same line Darney et al [ 44 ] in a study conducted in Mexico, to determine associations between age and patient-reported quality of family planning services among adolescents and young women, showed that although a lower proportion of adolescents reported long-acting reversible contraception (LARC) use, in comparison with young women, the adolescents using hormonal and LARC had significantly lower odds of reporting high-quality care compared with women aged 25–29. The role of family planning services is essential because the evidence supports that teenagers are more likely to choose a LARC method and continue with that method if they are offered [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same line Darney et al [ 44 ] in a study conducted in Mexico, to determine associations between age and patient-reported quality of family planning services among adolescents and young women, showed that although a lower proportion of adolescents reported long-acting reversible contraception (LARC) use, in comparison with young women, the adolescents using hormonal and LARC had significantly lower odds of reporting high-quality care compared with women aged 25–29. The role of family planning services is essential because the evidence supports that teenagers are more likely to choose a LARC method and continue with that method if they are offered [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We developed a new birth control decision aid, My Contraceptive Choice (MCC) 17,18 , aiming to fill the knowledge gaps among the young women in selecting appropriate contraceptive methods 20,21 , to accommodate their unique needs in contraceptive decision making, and to address the issues identified in the two existing contraceptive patient decision aids. We designed the MCC tool based on the CDC guidelines, additional medical literatures, the previous study on the two existing online tools, and the findings from a focus group 2,3,5,7,17,18,[21][22][23][24] . MCC focused on a list of contraceptive methods relevant to the target population, including condom 25 , copper IUD 26 , hormonal IUD 26 , ring 27 , mini pill 28 , combination pill 28 , implant 29 , patch 30 , shot 31 , and fertility awareness methods 32 .…”
Section: Development Of My Contraception Choice Toolmentioning
confidence: 99%
“…We designed the MCC tool based on the Centers for Disease Control and Prevention guidelines, additional medical literatures, the previous study on the two existing online tools, and the findings from a focus group. 2,3,5,7,17,18,[21][22][23][24] MCC focused on a list of contraceptive methods relevant to the target population, including condom, 25 copper IUD, 26 hormonal IUD, 26 ring, 27 mini pill, 28 combination pill, 28 implant, 29 patch, 30 shot, 31 and fertility awareness methods. 32 The functions of the MCC tool included three main sections: (1) a quiz to gather user preferences and prior experiences for specific contraceptive methods; (2) a sideby-side comparison of all contraceptive methods, with the customized recommendations highlighted; and (3) additional resources for educational purposes.…”
Section: Development Of My Contraception Choice Toolmentioning
confidence: 99%
“…Of the studies analyzed, two ( 26 , 30 ) reflect on the importance of training for IUD and LNG-IUS insertion being based on evidence and the skills of professionals, aiming for a clear training program and comprehensive practice. In line with this, the recent experience of training nurses in a municipality in Brazil consists of a theoretical component with a workload of 30 hours, followed by insertion training in a simulator, case discussion and consent form.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the competency of nurses to insert IUD, mentioned in the studies, it is highlighted that, upon acquiring it, nurses can positively influence the reproductive planning of adult and adolescent women, qualification of care, in addition to enabling training other nurses ( 15 , 26 , 28 , 30 ) , an aspect also considered an attribute of APN ( 35 ) , overcoming hegemonic models and physician-centered ( 15 , 26 , 28 , 30 ) . Research carried out in England, published in 1999, already revealed favorable evidence in this regard, highlighting that trained nurses perform efficient and safe IUD insertions, regardless of patients’ age, in addition to a better cost-benefit ratio ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%